SSB coaches understanding of the Filanesia Indonesian football coaching curriculum - Primasoni, Nawan; Pranoto, Ixsan Fajar; Arjuna, Fatkurahman; Karyono, Tri Hadi; Sriwahyuniati, Christina Fajar (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
The creation of quality players cannot be separated from the implementation of an appropriate football curriculum. The findings in the field, there are still many coaches who cannot understand the meaning of proactive, progressive, and constructive in playing, so that the children who play cannot practice filanesia in playing. Therefore, it is important to know the level of understanding of the coach of the Filanesia curriculum. This study aims to describe the level of understanding of Football School (SSB) coaches of the Indonesian football coaching curriculum Filanesia in Yogyakarta City. This research is a quantitative descriptive research. The population in this study were 50 SSB coaches in Yogyakarta City. The sampling technique used was purposive sampling. The criteria used in this study are as follows: (1) SSB coaches in the city of Yogyakarta who already have a coach's license, (2) SSB coaches who have attended Filanesia socialisation, (3) Willing to be a sample. Based on these criteria, a sample of 19 people was obtained. The data collection technique used a questionnaire. The instrument used is in the form of multiple choice questions. The instrument for the level of understanding of the Filanesia curriculum has a validity of 0.662 and a reliability of 0.934. Data analysis uses descriptive percentages. The results showed that the SSB coach's understanding of the Filanesia Indonesian football coaching curriculum in Yogyakarta City in 2022 was in the